High‐affinity von Willebrand factor binding does not affect the anatomical or hepatocellular distribution of factor VIII in rats. (24th August 2016) - Øie, C. I.; Roepstorff, K.; Behrens, C.; Bøggild Kristensen, J.; Karpf, D. M.; Bolt, G.; Gudme, C. N.; Kjalke, M.; Smedsrød, B.; Appa, R. S.
Abstract : Essentials Von Willebrand factor (VWF) stabilizes factor VIII (FVIII) and prevents its premature clearance. Rat anatomical and hepatocellular distribution studies assessed the VWF effect on FVIII clearance. Hepatocytes and liver sinusoidal endothelial cells play a key role in FVIII clearance. Anatomical and hepatocellular distribution of FVIII is independent of high‐affinity VWF binding. Abstract: Background: Von Willebrand factor (VWF) stabilizes factor VIII in the circulation and prevents its premature clearance. Objective: To study the effects of VWF on FVIII clearance in rats with endogenous VWF. Methods: Anatomical and hepatocellular distribution studies were performed in rats following intravenous administration of glycoiodinated recombinant FVIII (rFVIII) and a FVIII variant, FVIII‐Y1680F, lacking high‐affinity VWF binding. Radioactivity was quantified in organs, and in distinct liver cell populations. The role of VWF binding was also studied by immunohistochemical staining of rat livers perfused ex vivo with rFVIII alone or with a FVIII‐binding VWF fragment. Results: The liver was the predominant organ of rFVIII distribution, and a radioactivity peak was also observed in the intestines, suggesting FVIII secretion to the bile by hepatocytes. In the liver, ~60% of recovered radioactivity was associated with hepatocytes, 32% with liver sinusoidal endothelial cells (LSECs), and 9% with Kupffer cells (KCs). When calculated per cell, 1.5‐fold to 3‐fold more radioactivity was associated with LSECs than with hepatocytes. The importance of hepatocytes and LSECs was confirmed by immunohistochemical staining; strong staining was seen in LSECs, and less intense, punctate staining in hepatocytes. Minor staining in KCs was observed. Comparable anatomical and hepatocellular distributions were observed with rFVIII and FVIII‐Y1680F, and the presence of the VWF fragment, D'D3A1, did not change the FVIII staining pattern in intact livers. Conclusions: The present data support FVIII clearance via the liver, with hepatocytes and LSECs playing a key role. High‐affinity VWF binding did not alter the anatomical or hepatocellular distribution of FVIII.